Study of Water Discharge in Way Sikabiry Watershed, Liliboy Village, West Leihitu District, Central Maluku Regency - Serang, Rudi (International Journal of Advanced Engineering Research and Science, 2022)
The problem of flooding often hits Liliboy Village every rainy season, the problem of flooding is generally caused by poor drainage systems and a bigger impact is the result of damaged watersheds, watersheds that are supposed to be water conservation have undergone land use changes due to human intervention. The result of land use change that can be seen directly is that unpredictable discharge often occurs in the rivers where the watershed is damaged. For this reason, this study aims to determine the scouring pattern that occurs and the amount of water discharge in the Way Sikabiry watershed. This research was conducted in October 2019 in the Way Sikabiry watershed using the Profile (Cross Section) method, which is to place an unsinkable object on the surface of the river for a certain distance and record the time it takes for the floating object to move from one point of observation to another point of observation. have been done. The data used in this research include primary data such as river discharge data and secondary data in the form of watershed maps, measurements and drainage area.The results showed that the scouring pattern that occurred in the Way Sakabiry watershed resulted in a large downstream water flow but high flow rate while in the upstream it produced a small flow rate but a low flow rate and the amount of water discharge in the Way Sakabiri watershed upstream was 0.53095 m3. / second while in the downstream it is 0.73981 m3 / second.